The Peculiar Features of the New Religious Movements' Missionary Work in Contemporary Kazakhstan - Е V Korolyova (Vestnik Rossijskogo universiteta družby narodov. Seriâ Sociologiâ, 2010)
Nowadays foreign Protestant churches from the USA, South Korea, Sweden, France and Poland are carrying out missionary activities in the Republic of Kazakhstan. The crucial components of foreign religious missions are the establishment of the «missionary field», foreign sponsorship and the growth of religious communities. The author helms the reader to the analysis of social groups within the range of missionaries' sphere of influence as well as the channels and schemes of missionary work. The article is based on statistical data as well as the results of the sociological research conducted by the author.